Barriers and facilitators of risk‐based health care for adult survivors of childhood cancer: A report from the Childhood Cancer Survivor Study. Issue 3 (18th October 2019) - Ford, Jennifer S.; Tonorezos, Emily S.; Mertens, Ann C.; Hudson, Melissa M.; Casillas, Jacqueline; Foster, Barbara M.; Moskowitz, Chaya S.; Smith, Stephanie M.; Chou, Joanne F.; Buchanan, George; Robison, Leslie L.; Oeffinger, Kevin C.
Abstract : Background: Optimal risk‐based survivor health care includes surveillance for late effects and education targeted at reducing or preventing risky health behaviors. Understanding the reasons for a lack of risk‐based follow‐up care is essential. Methods: Adult participants from the Childhood Cancer Survivor Study were surveyed about having a cancer‐related visit in the past 2 years and the likelihood of having a cancer‐related visit in the future. Additional factors thought to be related to the primary outcomes were also assessed. Results: Nine hundred seventy‐five survivors completed the survey. Twenty‐seven percent (95% confidence interval [CI], 24%‐30%) had a cancer‐related medical visit in the previous 2 years, and 41% (95% CI, 38%‐44%) planned to have such a visit within the next 2 years. The likelihood of having had a cancer‐related visit within the last 2 years was higher among survivors assigning greater importance to these visits (relative risk [RR], 1.2; 95% CI, 1.1‐1.3), perceiving greater susceptibility to health problems (RR, 1.2; 95% CI, 1.1‐1.3), having a moderate to life‐threatening chronic health problem related to their cancer (RR, 2.1; 95% CI, 1.7‐2.7), seeing a primary care provider for a cancer‐related problem (RR, 1.3; 95% CI, 1.0‐1.6), having a cancer treatment summary (RR, 1.3; 95% CI, 1.0‐1.6), and endorsing greater confidence in physicians' abilities to address questions and concerns (RR, 1.2; 95% CI, 1.0‐1.3). Conclusions: Educational interventions improving awareness of treatment history and susceptibility to cancer‐related late effects and corresponding risk‐based care are likely to be beneficial for survivors of childhood cancers. Abstract : Among 975 adult survivors of childhood cancer, nearly three‐quarters reported no cancer‐related health care visit in the preceding 2 years. Survivors with health problems, primary care providers, and higher perceived susceptibility to late effects are more likely to be receiving or planning cancer‐related care; factors such as transportation and a lack of health insurance are unrelated to cancer‐related care.